Treatment of tardive dyskinesia: a review and update for dermatologists managing delusions of parasitosis. (3rd April 2022) - Cheng, Christian; Brownstone, Nicholas; Koo, John
Abstract: Introduction: This article introduces to the dermatology provider two medications for the treatment of tardive dyskinesia (TD), which were the first medications approved by the US FDA specifically for the treatment of TD. In addition to describing these two new medications, this article will also provide a focused review of the pathogenesis of TD, as well as non-FDA-approved treatments, which have been tried prior to the advent of these medications. Methods: A PubMed search was conducted and articles were reviewed by the senior authors and included if they were relevant for dermatologists regarding etiology, symptoms, risk, and treatment of TD. Results: One of the most widely accepted explanations of TD involves the concept of 'dopamine receptor hypersensitivity state.' There are several other less well substantiated proposed pathogenic pathways of TD. The clinical manifestation is characterized by involuntary movements. Prevention includes switching to a 2nd generation agent or using the lowest dose possible for the shortest amount of time. Two new FDA-approved medications for TD are also discussed and reviewed. Conclusion: TD now has FDA-approved medications for treatment. Now, there is even more reason for the dermatologist to have increased confidence when treating delusions of parasitosis (DOP) with antipsychotic agents.